ALLELOPATHIC IMPACT OF ESSENTIAL OIL OF TAGETES MINUTA ON COMMON AGRICULTURAL AND WASTELAND WEEDS - Arora, Komal; BATISH, DAIZY; KOHLI, RAVINDER K; SINGH, HARMINDER P (Innovare Journal of Agricultural Sciences, 2017)
ABSTRACT Objective: Tagetes minuta (Family Asteraceae) is an aromatic plant possessing volatile essential oil.Â Its oil finds extensive use in flavor and perfume industry. T. minuta oil also possess medicinal and insecticidal properties as antiheminthic, nematicidal, bactericidal, antiviral, fngicidal and insecticidal. The plant has been explored for herbicidal potential in very few reports. The aim of present study is to find out its allelopathic potential against common wasteland and agricultural weeds. Material & Methods: Various agricultural and wasteland weeds were selected for laboratory growth studies. Oil was applied in solution form using an emulsifier. Results: Growth of all test weeds was inhibited by T. minuta oil; however, effect was maximum in Amaranthus tricolor with complete inhibition at 1Âµl/ml and E. cruss-galli was least affected with complete inhibition at 5Âµl/ml concentration of T. minuta oil. Conclusion: T. minuta oil offers great potential for effective weed management in agricultural as well as wasteland areas. Â Keyowrds: Tagetes minuta, essential oil, allelopathy, solution form, wasteland, agricultural, weeds